Merlin's island - Guerra, Elisa Puricelli; Pernigotti, Chiara; Pernigotti, Chiara (North Mankato, Minnesota Stone Arch Books, a Capstone imprint, 2014)
The town of Pembrose in Cornwall, where Minerva, Ravi, and Thomasina live, is surrounded by places in the legends of King Arthur (which attract tourists), so when a famous archeologist arrives to debunk the legends, the three friends put aside the mystery of Minerva's identity and set out to prove that there really is magic in this place
English stories
a gift from book africa
1 2 13 15
Keywords: Arthur -- King -- Legends -- Juvenile fiction; Merlin -- (Legendary character) -- Juvenile fiction; Best friends -- Juvenile fiction